2010
DOI: 10.4103/0970-0218.69262
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes prevalence and its risk factors in rural area of Tamil Nadu

Abstract: Objective:To estimate the usefulness of the Indian diabetes risk score for detecting undiagnosed diabetes in the rural area of Tamil Nadu.Materials and Methods:The present study was conducted in the field practice area of rural health centers (Chunampett and Annechikuppam, Tamil Nadu), covering a population of 35000 from February to March 2008 by using a predesigned and pretested protocol to find out the prevalence and the risk of diabetes mellitus in general population by using Indian diabetes risk score.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 7 publications
9
53
4
2
Order By: Relevance
“…They also got a prevalence of 5.99% diabetes in their studied population where 56% cases of diabetes had high score. 7 In the present study 89 (42.38%) had family history of diabetes, in which 33 (37.08%) were diagnosed to be prediabetics and 11 (12.36%) were diabetics, and 121 (57.62%) did not have family history of diagnosed diabetics, among them 10 (8.26%) were diagnosed to be in prediabetic stage and 3 (2.48%) were diagnosed to be diabetics. A study conducted by Ramachandran et al on high prevalence of diabetes in an urban population in South India showed that 47% of the people who had diabetes had a positive family history, and the other study done by Gupta SK et al also showed that 31.50% had positive family history in diagnosed Type 2 Diabetes in urban population.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…They also got a prevalence of 5.99% diabetes in their studied population where 56% cases of diabetes had high score. 7 In the present study 89 (42.38%) had family history of diabetes, in which 33 (37.08%) were diagnosed to be prediabetics and 11 (12.36%) were diabetics, and 121 (57.62%) did not have family history of diagnosed diabetics, among them 10 (8.26%) were diagnosed to be in prediabetic stage and 3 (2.48%) were diagnosed to be diabetics. A study conducted by Ramachandran et al on high prevalence of diabetes in an urban population in South India showed that 47% of the people who had diabetes had a positive family history, and the other study done by Gupta SK et al also showed that 31.50% had positive family history in diagnosed Type 2 Diabetes in urban population.…”
Section: Discussionmentioning
confidence: 91%
“…In 616 respondents about 51 (8.27%) were diabetics. 7 Based on recommendations by American Association of Diabetes, a diagnosis of DM requires the presence of a fasting plasma glucose concentration of ≥126 mg/dL, or a 2 hour plasma glucose level of ≥200 mg/dL on an oral glucose tolerance test (OGTT). But later an international committee members selected by the American Diabetes Association (ADA) and the Alliance for European Diabetes Research (EURADIA) suggested that glycosylated hemoglobin (HbA1c) could be used as an alternative for making a diagnosis.…”
Section: Diabetesmentioning
confidence: 99%
“…7,8 Further use of such a risk score would be of great help in developing countries like India where there is a marked explosion of diabetes and over half of them remain undiagnosed. 9 About 26% of population had high risk score (>60) for diabetes in the present study. In a similar study conducted at Chennai by Mohan et al 10 43% of the population were found in high risk category and another study done in urban area of Pondicherry by Gupta et al 9 had 31.2% high risk subjects.…”
Section: Discussionmentioning
confidence: 77%
“…9 About 26% of population had high risk score (>60) for diabetes in the present study. In a similar study conducted at Chennai by Mohan et al 10 43% of the population were found in high risk category and another study done in urban area of Pondicherry by Gupta et al 9 had 31.2% high risk subjects. This risk difference may be due to variance in lifestyles of the population as our study was done in a rural area, whereas Mohan et al conducted the study in a metropolitan city and another study was in the urban area of Pondicherry.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation